Operation and control of a microgrid containing inertial and non-inertial micro sources - Majumder, R.; Shahnia, F.; Ghosh, A.; Ledwich, G.; Wishart, M.; Zare, F. (TENCON 2009 - 2009 IEEE Region 10 Conference, 2009)
In this paper, a new power sharing control method for a microgrid with several distributed generation units is proposed. The presence of both inertial and non-inertial sources with different power ratings, maximum power point tracking, and various types of loads pose a great challenge for the power sharing and system stability. The conventional droop control method is modified to achieve the desired power sharing ensuring system stability in a highly resistive network. A transformation matrix is formed to derive equivalent real and reactive power output of the converter and equivalent feedback gain matrix for the modified droop equation. The proposed control strategy, aimed for the prototype microgrid planned at Queensland University of Technology, is validated through extensive simulation results using PSCAD/EMTDC software.